Assessment of Type-2-Diabetics’ Patient Knowledge toward Diabetics’ Control Methods at Baghdad Teaching Hospital/ Medical City - Saad Abdul-Ridh Jissir (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study aims to assess the level of type (2)diabetic patients’ knowledge toward diabetes control methodsand to find out the relationship between diabetic patients’ knowledge toward diabetes control methods andtheir demographic characteristics that include (age, gender, and level of education). A quantitative descriptivestudy design was carried out at medical wards in Baghdad teaching hospital, for the period of January, 20th2019 to April 20th 2019, data was collected7th-30th March2019. The study sample is composed of (30)patients who were treated in medical wards at Baghdad Teaching Hospital. The questionnaire consists oftwo parts; first is concerned with the demographic and personal data for patients; and the second part isconcerned with patient knowledge toward diabetes control methods, that include diet, exercise and weightloss. The data have been analyzed through the application of: descriptive analysis that include frequency,percentages; mean of scores, and the inferential analysis that include: Analysis of variance and the researcherused the SPSS version 20 to analysis of data. The study identified that more than half of the study sample(53.3%) were male at age(45-64), in relation to level of education, most of the patients were illiterate. mostpatients have regular follow up, always use self- blood glucose monitoring practice, (73.3%) were receivinginformation about diabetes mellitus (DM). (83.3%) have information about diet. Polyuria and Hunger ismost specific signs and symptoms of hyperglycemia and hypoglycemia determined by patients, (66.7%)don’t have physical exercise and walking is chosen exercise of patient for 30< min in day. Most patient usehas diet adjustment especially in dinner meal. There is no significant difference between patient knowledgeand demographic characteristics.